A novel circular economy framework: assessing process circularity through resource flow and emissions analysis - Pilipenets, O.; Gunawardena, T.; Hui, F. K. P.; Mendis, P.; Aye, L. (2024)
The urgent need for more sustainable resource management highlights the imperative for innovative approaches within the circular economy paradigm. The knowledge gap addressed is the complexity of circular economy assessments and the need for robust frameworks to accurately evaluate circularity within processes. This article introduces a new framework to assess process circularity aimed at minimising environmental impacts, mitigating climate change, and fostering sustainability. Built upon a systematic literature review done in prior research, it combines the strengths of existing models and addresses their knowledge gaps. Central to this framework is the Process Circularity Index (ProCI), customisable to accommodate diverse sectoral requirements. By considering key components like materials, energy, water, and waste storage, the framework provides a holistic perspective on process circularity, aligning with the goals of promoting cleaner manufacturing practices. Practical implementation and testing of the framework in real-world are highlighted as future research avenues to demonstrate effectiveness and applicability.